2022
DOI: 10.3390/genes13122271
|View full text |Cite
|
Sign up to set email alerts
|

Can Polymorphisms in NLRP3 Inflammasome Complex Be Associated with Postmenopausal Osteoporosis Severity?

Abstract: The immune system plays a critical role in bone homeostasis and, consequently, in the pathophysiology of postmenopausal osteoporosis (OP) since estrogen deficiency induces the inflammasome and increases production of pro-inflammatory cytokines, such as IL-1β and IL-18. NLRP3 inflammasome complex genes have been related with bone homeostasis in cellular and animal models. Here, we performed an association study evaluating SNVs (single-nucleotide variants) in inflammasome NLRP3 pathway genes (NLRP3, CARD8, CASP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…NLRP3 inflammasome plays an important role in the development of osteoporosis by reducing differentiation, causing dysfunction of the osteoblasts, and accelerating osteoclasts, thus promoting bone resorption and impaired bone formation [122]. The study in postmenopausal women with osteoporosis demonstrated that single-nucleotide variants in NLRP3 inflammasome pathway genes activating pro-inflammatory cytokines IL-1β and IL-18 production are associated with osteoporosis severity [123]. Increased secretion of inflammatory cytokines, in particular, TNF-α and IL-1β, induces MAPK activation that leads to reduced osteoblastogenesis, resulting in defective bone remodeling [124].…”
Section: Inflammationmentioning
confidence: 99%
“…NLRP3 inflammasome plays an important role in the development of osteoporosis by reducing differentiation, causing dysfunction of the osteoblasts, and accelerating osteoclasts, thus promoting bone resorption and impaired bone formation [122]. The study in postmenopausal women with osteoporosis demonstrated that single-nucleotide variants in NLRP3 inflammasome pathway genes activating pro-inflammatory cytokines IL-1β and IL-18 production are associated with osteoporosis severity [123]. Increased secretion of inflammatory cytokines, in particular, TNF-α and IL-1β, induces MAPK activation that leads to reduced osteoblastogenesis, resulting in defective bone remodeling [124].…”
Section: Inflammationmentioning
confidence: 99%